THE EXIXTENCE OF THE OFFICIAL OF THE LAND DEED (PPAT) TO ASSISTS THE GOVERNMENT IN COLLECTIN THE ACQUISITION AND DIVERSION OF LAND AND BULDING (BPHTB) TO REALIZE LEGAL CERTAINTY - Mayfitrianthy; Jelly Nasseri (International Journal on Human-Computing Studies, 2021)
The official of the land deed is public official who authorized to make authentic deeds concerning certain legal act concerning the right to land or the property right of the flats unit. In the acquisition and diversion of land and bulding there is a arrangement before the parties sign the deed the official public of the land deed must ensure the duty on acquisition of land right is paid by the parties. The conclusion of this thesis is how the exsistance of PPAT to help government the menthod in this writing is empirical juridical which analyzed by authoritative theory and legal certainty, fieldwork ealted the PPAT and BPHTB. The results of this thesis about the exsistance of PPAT in assisting clients who make transaction for the acquisition or diversion of the land and the building in the deed. The exsistance of regulation stipulating that to signing a deed, BPHTB is paid in full by the parties. In assisting the government there are the consequence of the legal consequences imposed to PPAT if PPAT don’t violation in assisting the payment of BPHTB. Government should be with a new legislation governing the function of PPAT in BPHTB collection